Fiber-to-mortar bond behavior in TRM composites: effect of embedded length and fiber configuration - Dalalbashi, Ali; Ghiassi, Bahman; Oliveira, Daniel V.; Freitas, Ana (Elsevier, 2018)
The use of Textile Reinforced Mortar (TRM) composites for Externally Bonded Reinforcement (EBR) of reinforced concrete (RC) and masonry structures has attracted several attentions during the last years. The effectiveness of these composites in structural reinforcement is significantly dependent on the TRM-to-substrate and the fiber-to-mortar bond behavior. Despite the importance of the latter, that controls the crack distribution on these composites, have received few attentions and is relatively unknown.